The impact of changing people with sleep apnea using CPAP less than 4 h per night to a Bi-level device. Issue 6 (June 2015) - Gulati, Atul; Oscroft, Nicholas; Chadwick, Rebecca; Ali, Masood; Smith, Ian
Summary: Pressure intolerance is a reason for poor acceptance and subsequent compliance in some patients starting treatment with continuous positive airway pressure (CPAP). In unselected populations initiating CPAP; different types of pressure generating device have not been found to improve compliance. We hypothesized that using Bi-level PAP for patients who reported pressure related discomfort as a cause for poor compliance with CPAP might increase their hours of treatment use. Patients using CPAP <4 h/night with symptoms to suggest pressure intolerance were randomized to receive either a Bi-level PAP device or a new CPAP for 4 weeks. Following a washout period of 2 weeks, they were crossed over to the other device for 4 weeks. Twenty eight volunteers completed the protocol. Compared to the baseline (mean 1.49 h per night), improvement in compliance was noticed when changed to a new CPAP (2.23 h, p = 0.006) or Bi-level PAP (2.73 h, p < 0.001). The trend suggesting superior compliance with a Bi-level PAP device compared to new CPAP was not significant (p = 0.059) and there were no differences in subjective or objective measures of sleepiness. The results of this study suggest that routine intervention with Bi-level PAP in this group of sub-optimally compliant individuals was not very effective in improving PAP usage. There is however a subgroup of patients who complains of difficulty with exhalation; where favorable trends towards improved compliance were observed on Bi-level PAP.